Improving influenza vaccination uptake among healthcare workers by on-site influenza vaccination campaign in a tertiary children hospital - Melahat Melek Oguz (Taylor & Francis Group, 2019)
Children are at higher risk of influenza complications. The goals of this article are, estimating influenza vaccination coverage of Health Care Workers (HCWs) in tertiary children hospital, evaluating attitudes and practices of HCWs and evaluating whether HCWs vaccination uptake improved with onsite vaccination campaign. This was a before-after trial, which was carried out in a tertiary children hospital at 2017-2018 influenza season. The vaccination team visited all participants and collected information about previous vaccination uptake, attitudes and beliefs of HCWs by means of an anonymous questionnaire. Moreover, the influenza vaccine was offered onsite to all participants. A total of 572 HCWs participated in this study (response rate: 94.2%). Coverage was 10.8% in 2016-17 season and 39.9% in 2017-18 season (p < 0.0001). Multivariate regression analysis showed that being younger than 35 years (OR: 2.09), being vaccinated in previous season (OR: 47.02) and professional category of the participant (clinicians being reference group; OR: 1.73 for support staff and OR: 0.23 for nurses,) were significantly associated with vaccination uptake in 2017-18 season [95% CI]. None of the participants with former bad experience about vaccination was vaccinated in 2017-2018 season. And 90% of the participants having lack of knowledge about the vaccine were vaccinated in 2017-2018 season. After onsite vaccination campaign, influenza vaccination coverage improved significantly among HCWs. In order to achieve target vaccination coverage we should break down the prejudices with a comprehensive education program. Abbreviations: OR- Odds ratio; CI- confidence interval